Persistence Is Multi-Trait: Persistence Scale Development and Persistence Perseveration and Perfectionism Questionnaire into Polish Translation - Styk, Wojciech; Zmorzynski, Szymon; Samardakiewicz, Marzena (Brain sciences, 2023)
Persistence is defined as, among other ways, the need to achieve the goals and strive for the goal. Persistence can also be considered from the perspective of the resource concept, as a positive factor related to an individual’s adaptive behaviour, psychological resilience, and normal self-regulation. In contrast, tendencies behaviourally similar to perseverance, but which may have psychopathological features, are persistence and perfectionism. The main goal of our study was to: (I) Build non-clinical Persistence Scale (PS) in Polish and English; (II) translate in Polish and validate the Persistence, Perfectionism and Perseveration Questionnaire (PPPQ); (III) analyse properties of both scales. Methods: The study was conducted on a non-clinical group of 306 subjects. The mean age was 27.6 and ranged from 18 to 58 years. The properties of both scales were analysed using the NEO-FFI personality inventory, PSS-10 Perceived stress level scale, The UPPS-P Impulsive Behaviour Scale, the SPSRQ Sensitivity to Punishment and Reward scale, Grit scale and NAS-50 Self-Control Scale. Results: The psychometric features of the scales fulfil the requirements for psychometric tools. The factorial structure of both versions of the PS-20 scale proved to be unifactorial. Openness was the only variable to co-occur with the persistence scales of both the PS-20 and the PPPQ-10, and did not co-occur with scales intended to indicate psychopathology (Perseveration, Perfectionism). Negative correlations occurred with variables describing Persistence with levels of perceived stress, anxiety and depressive symptoms. Impulsivity measured by the SUPPS scale also showed negative correlations with the study variables. Conclusions: In the present work, we postulate that persistence is an umbrella construct that gathers and integrates many other traits to form a multi-trait persistence. Perseveration should be regarded as an undesirable trait characterising psychopathological behaviour. Desirable and indicative traits of an individual’s good functioning are persistence and, to some extent, perfectionism. Individuals with low persistence and high perseveration may be characterised by a repertoire of psychopathological behaviours.